A phenomenological interpretation of Biomimicry and its potential value for sustainable design - Klein, Lance (Kansas State University, 2009)
In this thesis, biomimicry is defined as imitating or taking inspiration from nature’s forms and processes to solve human problems (Benyus, 1997). As the design community realizes the tremendous impact human constructions have on the world, environmental designers look to new approaches like biomimicry to advance sustainable design. Building upon the claim made by biomimicry scientists that a full emulation of nature engages form, ecosystem, and process, this thesis uses a phenomenological approach to interpret human and environmental wholeness. Phenomenology broadens biomimicry’s scientific and technical focus on nature and considers how wholeness can be found among form, ecosystem, and process; and between people and environment. The thesis argues that, without a deeper, more responsive connectedness among people, nature, and built environment, any proposal for sustainable design will ultimately be incomplete and thus unsuccessful. In developing this phenomenological critique, the thesis reinterprets several environmental designs from the perspective of human and environmental wholeness: American architect Eugene Tsui’s hypothetical Ultima Tower; South African architect Michael Pearce’s Eastgate project in Zimbabwe; the Altamont Pass Wind Energy Development in California; Montana philosopher Gordon Brittan’s Windjammer wind turbine; American environmentalist David Orr’s Lewis Center at Ohio’s Oberlin College; and American architect Christopher Alexander’s Eishin campus in Japan. The collective claims developed in this phenomenological critique identify considerations and approaches that move beyond replacement technologies and systems to describe a way of environmental designing and making that is necessary for actualizing a more realistic sustainability in regard to both the natural and human-made worlds.
Keywords: biomimicry; sustainability; phenomenology; green design; Architecture (0729); Landscape Architecture (0390); Urban and Regional Planning (0999)